Complications in Lasers, Lights, and Radiofrequency Devices - AlNomair, Naief; Nazarian, Rachel; Marmur, Ellen (Facial Plastic Surgery, 2012)
Lights, lasers, and radiofrequency are unique sources of energy that are increasingly utilized for therapeutic and cosmetic purposes. As the indications for these tools continue to increase and their use expands beyond physicians to aestheticians, physician-extenders, and technicians, the incidence of complications has also risen. It is imperative that operators of these tools be as familiar with the management of potential complications as they are with their usage and indications. This article serves as a review of potential complications encountered with usage of lasers, lights, and radiofrequency devices in dermatology.
Keywords: lasers; complications; radiofrequency; side effects